Obstructive sleep apnea mouth breathing phenotype response to combination oral appliance therapy - Schramm, Preetam; Schneiderman, Emet; Hui, Jason; German, Zohre; Stenberg, William; Lin, Ju Ying (Frontiers in Sleep, 2024)
Introduction: Obstructive sleep apnea (OSA) is a multisystem physiological disorder of breathing during sleep that may contribute to systemic physiological imbalances and can also be exacerbated secondary to the use of some commonly prescribed medications. Methods: In a randomized parallel design trial, we included phenotypic mild to severe OSA mouth breathing subjects (n=36) confirmed by home polygraphy, to evaluate the efficacy of oral appliance plus mouth shield and oral appliance only during sleep on night-1 (T1), after 4- (T2) and 8-weeks (T3) with oral appliance therapy. Respiratory dynamics data were collected. Primary outcomes were: respiratory event index and mouth breathing. Anamnesis on medication intake was collected at enrollment. Results: Respiratory event index and the hypopnea index did not statistically differ between groups at T3. Oral appliance plus mouth shield and oral appliance only significantly reduced mouth breathing at T2 (p=.012) and T3 (p≤.001) compared with baseline. Exploratory analyses showed oral appliance plus mouth shield supine respiratory rate at T3 (p=.039) was marginally decreased compared with oral appliance only. The snore percent did not differ statistically between groups at T3. Oral appliance only showed a marginal oxygen saturation increase (p=.019) at T3 compared with oral appliance plus mouth shield. At T3, medication users had persistent respiratory events, mouth breathing and snoring compared with non-medication users. Logistic regression showed medication use may increase odds for mouth breathing (OR = 1.148; p =.015) and snoring (OR = 1.036; p = .049). Discussion: In our OSA-mouth breathing cohort, oral appliance only was similar to oral appliance plus mouth shield in attenuating the respiratory event index, hypopnea index and mouth breathing at 8-weeks. Oral appliance only increased oxygen saturation at T3, while oral appliance plus mouth shield maintained a relatively narrow oxygen saturation range from T1 – 3. Oral appliance plus mouth shield marginally lowered the supine respiratory rate at T3 compared with oral appliance only. Persistent respiratory events, mouth breathing and snoring were observed in medication users at T3.